Calculation Method for Underground Metal Corrosion Due to Stray Current Based on Ground Potential Distribution - TANG Yuhang, YU Kun, ZENG Xiangjun, NI Yanru, CHENG Xinxiang, HAN Wei (Shanghai Jiaotong Daxue xuebao)
Urban rail transit construction plays an important part in supporting the “dual carbon” goals and accelerating the development of new-type power system. However, stray currents generated during subway operations can lead to soil polarization and corrosion of buried metal pipelines. To analyze the impact of stray currents on buried metal pipelines, a method is proposed to calculate the corrosion current density of buried pipelines based on ground potential distribution. First, a long-line four-layer grounding network reflux model with multiple trains is established based on the actual subway traction power supply system, which enables the real-time dynamic calculation of stray current distribution and rail potential. Next, the rail potential distribution is treated as a line voltage source, which is integrated into the subway line model to calculate ground potential distribution. Then, a soil-pipeline circuit model including anti-corrosion coating is established to realize dynamic calculation of pipeline corrosion current density based on ground potential distribution. Finally, the influencing factors of the pipelines corrosion current density are studied, such as rail direct current (DC) resistance, transition resistance, and soil resistivity. The simulation results show that the pipeline corrosion current density is linearly related to rail DC resistance. When the transition resistance between the rail and the drainage network increases from 5 Ω·km to 50 Ω·km, the corrosion current density of the two buried pipelines reduces by 65.94% and 67.45%, respectively. Additionly, a higher soil resistivity has a certain inhibitory effect on stray current propagation, providing a degree of mitigation against corrosion.